พฤติกรรมการอ่านงานวิจัยและเจตคติต่อการวิจัยของนักศึกษาครู - แผนพรหม, กรวุฒิ; ว่องวาณิช, สุวิมล (An Online Journal of Education, 2018)
Research reading behavior is significantly essential for teacher students; enhancing learners’ critical and research skills. The more they have read the varieties of research, the more quality of their researches will be developed. The purpose of this research was to compare research reading behavior and attitude toward research of teacher students in different major. The samples were 146 of third year teacher students studying research and statistic for learning development. The research instrument was research reading behavior questionnaire, consisting of 3 indicators: 1) the amounts of research reading expectation 2) the amounts of research reading and 3) the period of time for research reading (fill in the blank) and attitude toward research factor was rating scale. The statistics used in this research were mean, standard deviation and one-way ANOVA. The finding, found that the difference of the amounts of research reading expectation and the amounts of research reading are statistically significantly at .05 level but the results of the period of time for research reading and the attitude toward research is not different statistically significant in general.